Evaluation of a Development of an Internet Learning Program on Epidemiology for Surveillance and Rapid Response District Team in Health Inspector Region 14 - Sansiritaweesook, Getsara; Banlue, Choochart; Sankot, Niphol; Limpawittayakul, Manasanum; Limpawittayakul, Wachirawit; Trichaisri, Nichapa (Journal of Health Science of Thailand, 2017)
Epidemiology is considered a cornerstone methodology of public health research, and is highly regarded in evidence-based medicine for identifying risk factors for disease and determining optimal treatment approaches to clinical practice. The epidemiology knowledge is significant to the epidemiology personnel so that means to the knowledge enhancement are of great importance. Computer media is one of the best to deliver knowledge, moreover, learners could prioritize to their ability. Learners are able to choose their courses. To avoid weary coursework, and reduce cost of seminar, web-based tutorial is one of the best materials for epidemiology for health care personnel especially with Surveillance Rapid Response Team (SRRT). Furthermore, this could apply for all students including an interested group who apply epidemiology science. The purposes of this research were aimed at obtaining, enhancing the efficiency of web based tutorial, comparing between pre-test and post-test scores, and studying the learners satisfaction on epidemiology. The research design were quasi-experimental study on Surveillance and Rapid Response District Team of health inspectors region 14 in fiscal year 2008. In order to achieve the above objective, the inspectors divided 126 persons of SRRT in Health inspector region 14 by their past experiences into 4 sample groups which could be categorized as high, moderate, low, and non-experienced and samples were selected randomly. Before the analytical process, the researchers had previously modified research instrument for quality verification twice and in the second pilot experiments, it yielded results as 82.7 and 84.3 percent consecutively. The other tools were designed to measure the test result, course exercise, and satisfaction test. It was shown that 109 persons or 86.5 percent of the target completed the training modules as required. Moreover, the results indicated that post-test score was higher than pre-test score with statistically significant difference at the level 0.05 (p>0.05). Nevertheless, the efficiency of the tutorial web-based instruction was 82.3 and 85.2 percent consecutively, and 51.4 percent of the samples were satisfied with the web base instruction. In conclusion, the web-based tutorial instruction is an effective web instruction for self-learning practice of SRRT and learners as planned. It is recommended that a multimedia system, motion simulation pictures and interactive summarized lessons could enhance even the efficiency of the tool, and become instrumental in network development.